2014
DOI: 10.1039/c4ra07817a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles entrapped in the cross-linked poly(imidazole/imidazolium) immobilized Cu(ii): an effective heterogeneous copper catalyst

Abstract: Anchoring of copper sulfate in layered poly(imidazole-imidazolium) coated magnetic nanoparticles provided a highly stable, active, reusable, high loading, and green catalyst for the click synthesis of 1,2,3-triazoles via a one-pot cycloaddition of alkyl halide, azide, and alkyne (Cu-A3C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 47 publications
(42 reference statements)
0
28
0
Order By: Relevance
“…It is worth mentioning that the results showed alkyl and aryl halides react better than haloketones in terms of yields and reaction times. The efficiency of CuI@[PMMA‐co‐MI] in click reaction was also compared with that of previously reported catalysts under various reaction conditions (Table ) . By comparison, it can be concluded that CuI@[PMMA‐co‐MI] as a novel nanocatalyst has several merits such as higher or comparable yield of the desired product in shorter reaction time.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is worth mentioning that the results showed alkyl and aryl halides react better than haloketones in terms of yields and reaction times. The efficiency of CuI@[PMMA‐co‐MI] in click reaction was also compared with that of previously reported catalysts under various reaction conditions (Table ) . By comparison, it can be concluded that CuI@[PMMA‐co‐MI] as a novel nanocatalyst has several merits such as higher or comparable yield of the desired product in shorter reaction time.…”
Section: Resultsmentioning
confidence: 95%
“…Next, other reaction variables, such as catalyst loading amount and temperature, were examined (Table ). The optimal reaction conditions in terms of higher yields and shorter reaction times as well as considering the principles of green chemistry were found to be as follows: benzyl bromide, phenylacetylene (1 mmol) and sodium azide (1.3 mmol) being reacted in the presence of CuI@[PMMA‐co‐MI] (0.02 g) in water (10 ml) at room temperature (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 9 6) due to steric hindrance. The Suzuki reaction of sterically hindered 2-bromonaphthalene afforded a moderate yield of the corresponding coupled product.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…With the advent of nanoscience, chemists achieved that the best solution to lower activity limitation of heterogeneous catalysts is to keep the size of the particles in the heterogeneous catalyst as small as possible. Nowadays a wide variety of nanostructured catalysts or catalytic systems immobilized on nanostructured supports have been applied in various catalytic reactions and as results heterogeneous catalytic systems recently have attracted much attention [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…An innovative way for increasing the loading amounts of nickel is immobilization of metal ions onto the cross‐linked polymeric networks . These polymeric networks have high porosity, high surface area and large amounts of attaching sites to grab metal ions .…”
Section: Introductionmentioning
confidence: 99%